Miasis Urogenital: Tinjauan Sistematis Literatur pada Irisan Urologi dan Entomologi - Ishaq, Muhammad Rozaqy; Fitria Dewi Puspita Anggraini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Urogenital myiasis (UGM) is a rare parasitic disease at the intersection of urology and medical entomology, caused by infestation of the urogenital tract with dipterous fly larvae. Despite its low prevalence, UGM poses significant diagnostic and therapeutic challenges. To systematically review the epidemiology, causative agents, clinical manifestations, diagnosis, and management of urogenital myiasis based on published literature from 2015 to 2025. A comprehensive literature search was conducted using PubMed, Scopus, and Google Scholar databases for articles published between 2015 and 2025. Keywords included